Taxonomic novelties and synopsis of the genus Digitaria (Poaceae, Panicoideae, Paniceae) in Puerto Rico and the Virgin Islands - Vega, Andrea Susana (2018)
Fil: Vega, Andrea Susana. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Recursos Naturales y Ambiente. Cátedra de Botánica General. Buenos Aires, Argentina.